Evaluation of anti-inflammatory and healing activity of a nano-structured lipid carrier containing tucuman butter oil and butter - Rossato, Aline; Silveira, Larissa da Silva; Oliveira, Pâmella Schramm; Souza Filho, Walter Paixão de; Wagner, Roger; Klein, Bruna; de Souza, Diego; Baldissera, Matheus Dellaméa; Sagrillo, Michele Rorato (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
The Amazon region has a wide variety of native palm trees that have fruits and oilseeds. Among these palm trees, Pará tucumã (Astrocaryum vulgare) stands out, which provides the tucumã fruit from which its oil is extracted, which has anti-inflammatory, antioxidant, healing and antibacterial properties, among others. However, oils, like that of tucumã, are sensitive to thermal degradation, as well as oxidative reactions, which can reduce their pharmacological effectiveness. In this way, nanotechnology can be a tool to preserve the pharmacological properties of essential oils and increase their therapeutic effectiveness. Therefore, this study aims to develop a nanostructured lipid carrier (NLC) containing tucumã butter and oil, to analyze its in vitro properties of anti-inflammatory and healing activity. For that, tests of anti-inflammatory activity and healing activity were performed by the Scratch test in vitro. The results of the tests demonstrated that the majority of the NLC concentrations showed anti and pro-inflammatory and healing activity.